Genetic Structure of Northern Bobwhites in Northeast Mississippi and Southwest Tennessee - Kristine O. Evans; Loren W. Burger Jr.; William E. Palmer (National Quail Symposium Proceedings, 2017)
Precipitous declines in northern bobwhite (Colinus virginianus) populations across most of the natural range may increase susceptibility to genetic isolation, restrict gene flow among subpopulations, and exacerbate vulnerability to catastrophic stochastic processes. We characterized the level of genetic variability of 223 individual bobwhites representing 4 disjunct populations in northeast Mississippi and southwest Tennessee in 2002. Analyses at 8 microsatellite loci suggested observed heterozygosity was lower than expected but showed no significant heterozygosity excess. Estimates of FIS coefficients were positive in each subpopulation, but low overall, suggesting only minor loss in heterozygosity over the entire population. Gene diversity was high and genetic differentiation within and among subpopulations and isolation by distance effects were minimal, suggesting adequate levels of gene flow. We suggest, despite population losses, gene flow is maintained among subpopulations, which may reflect the bobwhite’s ability to disperse successfully in the agricultural landscape in this region. Maintenance of gene flow across seemingly inhospitable landscapes suggests focal area management directives may enhance population sustainability. Greater understanding of the genetic structure of northern bobwhite populations on larger geographic scales and across the species’ range is paramount to population recovery.
Keywords: Colinus virginianus; genetic structure; Mississippi; northern bobwhite; population genetics; Tennessee